Optimasi Produksi Dengan Menggunakan Sucker Rod Pump (SRP) Pada Sumur “Z” Di Lapangan Kalrez Petroleum Seram Ltd - Sherlina Akihary; Henk Subekti; Alexander A Patty (Journal Mechanical Engineering, 2023)
In the oil and gas production process, operating production wells are mainly based on good production capacity to achieve the best production. However, over time, well production causes the pressure in the well reservoir to drop to such an extent that the well no longer has the ability to flow fluid naturally from the reservoir to the surface. Research by Karlez Petrolum (Seram) Ltd. Karlez himself uses an artificial lift (sucker rod pumps), SRP is one of the artificial lift techniques used to help lift oil from the well to the surface. It is necessary to optimize the production of more optimal wells for the pump installed in the “Z” Well in the Karlez Petroleum (Seram) Ltd. field. To obtain the desired profit, the costs incurred must be less than the income earned. This can be seen from economic indicators.  Keywords: Sucker Rod Pump, Optimization, artificial lift, economic indicators.